Penyebab Kebakaran Hutan di Kawasan Hutan Pendidikan Gunung Walat, Jawa Barat - Ati Dwi Nurhayati; Aldi Yusup (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Forest fires resulted from human activities such as land preparation by using fire. Dry season, forest fire hazard, low awareness of local communities as well as limited infrastructure for fire control are all the factors related to the occurrence of forest fires. The objectives of this research is to identify forest fire causes in Gunung Walat Educational Forest. Forest fire in Gunung Walat Educational Forest over the last five years (2011-2015) occurred in 2012, 2014 and 2015. Forest fire in 2015 had the highest frequency that is three times with the area burnt reached 8.4 ha. The rainfall in Cibadak District is relatively high but it contain some months with the low rainfall. There is a correlation of some parameters that analyzed between characteristic of respondent with the occurrence of forest fire. Characteristic of respondent such as employment, income and distance to forest in Batununggal village showed a positive correlation to the forest fire occurrence. Key words: characteristic of respondent, forest fire, rainfall